KARAKTERISASI DAN IDENTIFIKASI GENUS BAKTERI ENDOFIT DARI DAUN DAN BATANG JERUK SIAM (Citrus nobilis var. microcarpa) SEHAT DI DESA ANJUNGAN KALIMANTAN BARAT - Silalahi, Lusiana Fitriani; Mukarlina, Mukarlina; Rahmawati, Rahmawati (Universitas Tanjungpura, 2020)
Endophytic bacteria that live in the tissues of plant organs act as biological control agents and growth accelerator such as for plants Siam Orange (Citrus nobilis var. microcarpa) which is included in main commodity horticultural crops in West Kalimantan. This study was aimed to know the genera of endophytic bacteria from healthy Siam Orange stems and leaves. The study was conducted through the steps of endophyte bacteria isolation, and identification. Systematic sampling method was used and data collected were descriptively analyzed. The study results obtained nine isolates from leaves of Bacillus, Micrococcus, Pseudomonas, Erwinia, Microbacterium, Cellulomonas and one unidentified isolate, one isolate from stems of Micrococcus.